Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1634/theoncologist.2013-0305
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Cervical Cancer Screening and Treatment in Tanzania: Stakeholders’ Perceptions of Structural Influences on Scale-Up

Abstract: Tanzania has the highest burden of cervical cancer in East Africa. This study aims to identify perceived barriers and facilitators that influence scale-up of regional and populationlevel cervical cancer screening and treatment programs in Tanzania. Convenience sampling was used to select participants for this qualitative study among 35 key informants. Twenty-eight stakeholders from public-sector health facilities, academia, government, and nongovernmental organizations completed in-depth interviews, and a seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…The reasons for postponing cryotherapy among women eligible for the see‐and‐treat approach were mainly related to logistic constraints such as an irregular gas supply, low maintenance of cryotherapy devices, and shortage of trained healthcare workers. Similar barriers have been reported in Tanzania and Burkina Faso, highlighting the need for sufficient and sustained financial support dedicated to this screening activity in participating facilities . To overcome some of these challenges, the introduction of thermocoagulation as an alternative to cryotherapy might mitigate the issue of gas supply and device maintenance, as previously demonstrated in Malawi .…”
Section: Discussionmentioning
confidence: 61%
“…The reasons for postponing cryotherapy among women eligible for the see‐and‐treat approach were mainly related to logistic constraints such as an irregular gas supply, low maintenance of cryotherapy devices, and shortage of trained healthcare workers. Similar barriers have been reported in Tanzania and Burkina Faso, highlighting the need for sufficient and sustained financial support dedicated to this screening activity in participating facilities . To overcome some of these challenges, the introduction of thermocoagulation as an alternative to cryotherapy might mitigate the issue of gas supply and device maintenance, as previously demonstrated in Malawi .…”
Section: Discussionmentioning
confidence: 61%
“…In sub-Saharan Africa, decentralisation is a key facilitator for initiating regional programmes for cervical screening (McCree et al 2015 ). In our data, however, the high occupational profile of attending women suggested that socioeconomic selection factors are frustrating, at least in part, our efforts to target the rural population.…”
Section: Discussionmentioning
confidence: 99%
“…These initiatives aim at achieving one of the goals of the National Cancer Control Strategy—2013–2022 of reducing the burden (morbidity, disability and premature mortality) related to non‐communicable diseases in Tanzania by 20% by 2020 (United Republic of Tanzania Ministry of Health & Social Welfare, ). The initiatives also intend to achieve the goal of non‐communicable diseases (NCD) strategic plan to control and prevent cancer for 2016–2020, which is 50% increase in proportion of patients detected with early‐stage cancer (McCree et al, ; Moshi et al, ; United Republic of Tanzania, Ministry of Health, Community Development, Gender Elderly & Children, ). In addition, the MoHCDGEC established the Reproductive Health‐Cancer Unit to deal with cervical cancer (Moshi et al, ).…”
Section: Introductionmentioning
confidence: 99%